2020
DOI: 10.1029/2020ja028364
|View full text |Cite
|
Sign up to set email alerts
|

Multipoint Conjugate Observations of Dayside ULF Waves During an Extended Period of Radial IMF

Abstract: Long-lasting Pc5 ultralow frequency (ULF) waves spanning the dayside and extending from L ∼ 5.5 into the polar cap region were observed by conjugate ground magnetometers. Observations from MMS satellites in the magnetosphere and magnetometers on the ground confirmed that the ULF waves on closed field lines were due to fundamental toroidal standing Alfvén waves. Monochromatic waves at lower latitudes tended to maximize their power away from noon in both the morning and afternoon sectors, while more broadband wa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 73 publications
(91 reference statements)
1
14
1
Order By: Relevance
“…Another point we would like to emphasize is the unique role of ULF wave activity as a direct driver of intense geoelectric fields during geomagnetic storms. Note that the drivers of ULF waves vary from external sources such as IP shocks to internal sources such as particle injections during substorms (Shi et al, 2018(Shi et al, , 2020. However, these external and internal sources can also drive intense geoelectric fields via mechanisms other than ULF waves.…”
Section: Discussionmentioning
confidence: 99%
“…Another point we would like to emphasize is the unique role of ULF wave activity as a direct driver of intense geoelectric fields during geomagnetic storms. Note that the drivers of ULF waves vary from external sources such as IP shocks to internal sources such as particle injections during substorms (Shi et al, 2018(Shi et al, , 2020. However, these external and internal sources can also drive intense geoelectric fields via mechanisms other than ULF waves.…”
Section: Discussionmentioning
confidence: 99%
“…These are low‐m toroidal waves which have been investigated in Shi et al. (2020) and are beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 98%
“…Note that Pc5 waves were present in GPS TEC (Figures 2g and 2h), ground magnetometer (Figures 2g-2i), and GOES observations (Figure 3a). These are low-m toroidal waves which have been investigated in Shi et al (2020) and are beyond the scope of this study.…”
Section: Discussionmentioning
confidence: 99%
“…The cusp has been the subject of numerous observational (e.g., Lavraud et al., 2005 ; Nykyri et al., 2012 ; Pitout et al., 2009 ; Taylor et al., 2004 ) and simulation studies (Omidi & Sibeck, 2007 ; Palmroth et al., 2013 ; X. Y. Wang et al., 2009 ) under different IMF conditions. Under IMF with a strong radial component, the cusp has been observed to be highly dynamic (Taylor et al., 2004 ), and it has been shown that the turbulence in the ion foreshock can lead to ULF waves on the open and closed field lines of the polar cap (Shi et al., 2020 ). Other statistical observations have shown the structure of the cusp and its boundaries under various IMF conditions (Lavraud et al., 2004 , 2005 ; Pitout et al., 2012 ), and statistical studies of cusp structure and motion are shown in (Pitout et al., 2006 , 2009 ).…”
Section: Introductionmentioning
confidence: 99%